Security for Wireless Sensor Networks - Liu, Donggang; Ning, Peng (Advances in Information Security, 2007)
Wireless sensor networks have recently received a high level of attention due to their wide applications in military and civilian operations. Security for Wireless Sensor Networks discusses fundamental security issues in wireless sensor networks, techniques for the protection of such networks, as well as results from recent studies in wireless sensor network security. This volume assists both professionals and students to understand background knowledge in wireless sensor network security and prepare them for producing research in this domain. Security for Wireless Sensor Networks is designed for a professional audience composed of researchers and practitioners in industry. This book is also suitable as a secondary text for graduate-level students in computer science.